Hemoglobin Concentration May Affect the Effect of Atorvastin on Chronic Subdural Hematoma After Burr-Hole Drainage at High Altitude - Wei, Linjie; Lin, Chi; Zhong, Mingfeng; Zhang, Jianbo; Zhu, Gang (Frontiers in Neuroscience, 2020)
Objective: Chronic subdural hematoma (CSDH) is a common disease. Atorvastatin calcium can increase CSDH absorption. However, whether atorvastatin can increase hematoma absorption and reduce recurrence at high altitudes is not clear. Methods: After burr-hole drainage, CSDH patients were divided into an atorvastatin group and a control group. Follow-up CT was performed on day 1, month 1, month 2 and month 3 after surgery. Then, the recurrence rate, poor therapeutic effect, time to recurrence, poor surgical result, recurrence with operation, CSDH volume and Markwalder grading scale score(MGSS) were calculated, and related risk factors were analyzed. Results: The logistic regression analysis showed that hemoglobin concentration(HB) (odds ratio, 1.138; 95% CI, 1.038 to 1.247 in the control group, odds ratio, 1.126; 95% CI, 1.029 to 1.233 in the atorvastatin group) and low-density time (odds ratio, 3.527; 95% CI, 1.420 to 8.735 in the control group, odds ratio, 2.529; 95% CI, 1.103 to 5.799 in the atorvastatin group) were possible risk factors for the two groups. The ROC curves showed that the AUC values for the Hb, CT value (Hu) and low-density time were 0.812, 0.702 and 0.755 for all subjects, 0.812, 0.719 and 0.790 for the control group, and 0.807, 0.682 and 0.756 for the atorvastatin group, respectively. The postoperative follow-up results showed that there was no significant difference in the recurrence rate, poor therapeutic effect, time to recurrence, poor surgical result, recurrence with operation, CSDH volume or MGSS between the two groups. Conclusion: The effect of atorvastatin was not significant after the operation. The risk factors for CSDH recurrence were the Hb and low-density time. The Hb was the most specific and sensitive predictor of CSDH recurrence.